Paranoia - Patterson, James 1947-; Born, James O. (New York : Little, Brown and Company, 2025)
"At every death scene, Bennett says a prayer over the victim. But recently, too many of departed have been fellow cops. 'I want you to look at these deaths on special assignment,' NYPD Inspector Celeste Cantor says. 'Report only to me.' Bennett excels as a solo investigator. But he's chasing a killer who feeds on isolation--and paranoia"--
115722
Keywords: Bennett, Michael -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Police -- Crimes against -- Fiction; Serial murder investigation -- Fiction; Thrillers / Crime; Mystery & Detective / Police Procedural; Suspense; New York (N.Y.) -- Fiction; Mystery fiction; Suspense fiction; Thrillers (Fiction); Novels